Motivation and Learning English: A Study on Nepalese Public High School Learners - Laudari, Suman (Journal of NELTA, 2015)
Motivation is long found to be an important factor to affect the task of learning an L2 as it provides the stimulus required to initiate and sustain the task of learning the L2. It is even argued that if learners are motivated, they are likely to succeed in the task of language learning regardless of other factors. The present study examined the Nepalese public high school learners’ motivation to learn English. Based on Dörnyei’s (2005; 2009) second language (L2) motivational Self System as the theoretical framework, this study employed a 64 item questionnaire to collect the data. Correlation and regression were carried out to establish that the main factors affecting learners’ English language learning motivation were attitude to learning English and ideal L2 self. However, ought-to L2 self did not contribute to learners’ motivation directly, which is on the contrary to the findings of the study done in Asian contexts previously. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12084 Journal of NELTA, Vol 19 No. 1-2, December 2014: 99-116